Efecto de los créditos financieros en el nivel de empleo del Departamento de Loreto 2017-2022 - Cuje Tuituy, Ronal (2024)
The present research is quantitative, causal level and non-experimental design with longitudinal data. The study population was considered to be the monthly statistical records of financial credits and the level of employment of the economically active population in the department of Loreto from January 2017 to December 2022. Financial credits were classified as those granted by universal banks, municipal banks and other financial institutions, among which were credit companies, financial companies and state entities. After applying a simple linear regression econometric model, it was determined that an increase of 1% in the monthly variation of credits granted by institutions in the formal financial system generates, eleven months later, an increase of 0.22% in the level of employment in the department of Loreto during the period 2017 2022. Furthermore, it was found that the independent variable explains 17.74% of the behavior of the dependent variable. With respect to the indicators of the dependent variable, a significant positive estimated effect was only found in the monthly variation of credits granted by universal banking institutions.